Health insurance provider and endovascular treatment availability are associated with different hemodialysis vascular access profiles: A Brazilian national survey - Franco, Ricardo Portiolli; Chula, Domingos Candiota; de Moraes, Thyago Proença; Campos, Rodrigo Peixoto (Frontiers in Nephrology, 2022)
In Brazil, most hemodialysis (HD) patients are treated by the country’s public health system. However, accessibility to healthcare is different for public and private patients. This study aimed to identify the profile of vascular access in a Brazilian HD sample. Additionally, it aimed to examine the influence of public and private health insurance, accessibility to endovascular treatments, and timely arteriovenous access creation on the prevalence of tunneled catheters (TCs), non-tunneled catheters (NTCs), and arteriovenous (AV) access. We conducted a cross-sectional electronic survey across 834 centers. Centers were inquired about the number of patients with public and private health insurance, the profiles of vascular access, time for AV access creation, accessibility to TC insertion and endovascular treatments, and the availability of peritoneal dialysis and kidney transplantation. Logistic regression and multilevel logistic regression were performed to evaluate possible interactions between the independent variables. A total of 7,973 patients across 47 HD centers were included in the survey. Public health patients accounted for 77% of the study sample. The overall vascular access profiles of the public and private insurance groups were significantly different (p < 0.001). For patients with public health insurance, the prevalence of any catheter was 25%, while that for private patients was 31.8% (p < 0.001). The prevalence of TCs was more common in private patients (15.3% vs. 23.1%, p < 0.001). AV accesses were more common in public health patients (75% vs. 68.2%, p < 0.001), as were fistulas (72.4% vs. 63.1%, p < 0.001). AV grafts were more prevalent among patients with private insurance (2.6 vs. 5.1%, p < 0.001). The availability of endovascular treatments increased the chance of having a TC by 2.3-fold (OR = 2.33, 95% CI = 1.30–4.18); however, it did not reduce the chance of having any catheter. A high chance of having a catheter was found when the time to AV access creation exceeded 60 days. The differences between public and private patients may be explained by underpayments and the decreased accessibility to care infrastructure in the public system, especially for endovascular treatments. In this sample, public health patients had a decreased risk of having a TC over an NTC. Differences in care accessibility and insurance type might influence the type of vascular access.